Strategi Guru dalam Penggunaan Bahasa untuk Meningkatkan Kemampuan Belajar Anak Usia Dini di TK Pembina Mataram - Dwi Rahmawati Saputri; Antonius Suhendra (Journal of Language Studies, 2026)
This study examines teachers’ language use strategies in improving early childhood learning abilities at TK Pembina Mataram. Language plays a crucial role in shaping children's cognitive, social, and communication skills during early development stages. The objective of this research is to identify and analyze effective teacher strategies in language use to enhance learning outcomes. This study employed a qualitative descriptive approach, involving classroom observations, interviews, and documentation. The findings reveal that teachers utilize various strategies such as storytelling, singing, role-playing, interactive questioning, and the use of educational media to stimulate children's language development. These strategies significantly enhance children's vocabulary, comprehension, and communication skills. The results are consistent with previous studies highlighting the effectiveness of interactive and play-based language approaches in early childhood education. Furthermore, teacher competence in language use contributes to children's positive language attitudes and character development. The study concludes that systematic and interactive language strategies are essential in optimizing early childhood learning processes. These findings provide practical implications for educators to design more effective language-based learning strategies in early childhood education settings.